Inspiring architects in the application of design for all: knowledge transfer methods and tools (Journal of Accessibility and Design for All, 2019)
Accessibility is often translated in design practice by means of a prescriptive approach, focusing on legislation’s application, instead of understanding the real needs and wishes of users. On the contrary, the descriptive and performance-based approach of Design for All can help architects in designing inclusive environments. Therefore, it is fundamental to translate the existing theory into information that meets the architects’ needs to link knowledge and practice. This study  focuses on methods to inspire and support architects applying a Design for All strategy by gathering information and advice. In particular, the paper demonstrates a literature review to identify how to transfer design guidelines to architects. Based on the analysis of the included papers, four criteria were defined to translate Design for All information from users’ needs into design indications for architects in a descriptive way. The current results will provide the basis for developing a tool to inspire and create awareness for architects on Design for All in architectural practice.